Eutrophication in Coastal Ecosystems 2009
DOI: 10.1007/978-90-481-3385-7_20
|View full text |Cite
|
Sign up to set email alerts
|

Modeling eutrophication and oligotrophication of shallow-water marine systems: the importance of sediments under stratified and well-mixed conditions

Abstract: A one-dimensional model that couples water-column physics with pelagic and benthic biogeochemistry in a 50-m-deep water column is used to demonstrate the importance of the sediment in the functioning of shallow systems, the eutrophication status of the system, and the system's resilience to oligotrophication. Two physical scenarios, a well-mixed and a stratified water column, are considered and both are run along a gradient of increasing initial pelagic-dissolved inorganic nitrogen (DIN) concentration. Where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Because of its storage capacity for particulate and dissolved components, sediment is an important reservoir and by slowly exchanging material with the overlying water, may influence long-term system behavior. Soetaert and Middelburg (2009) explored the response of hypoxic coastal systems to lowered nitrogen loadings and concluded that internal nitrogen loading (sediment nitrogen release) delays nitrogen restoration. Similar delays in system recovery to reduced-phosphorus loadings by internal loading in the sediment have been shown for certain lakes (Jeppesen et al, 2005).…”
Section: Duration Of Exposure To Hypoxia Matters For Biogeochemical Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its storage capacity for particulate and dissolved components, sediment is an important reservoir and by slowly exchanging material with the overlying water, may influence long-term system behavior. Soetaert and Middelburg (2009) explored the response of hypoxic coastal systems to lowered nitrogen loadings and concluded that internal nitrogen loading (sediment nitrogen release) delays nitrogen restoration. Similar delays in system recovery to reduced-phosphorus loadings by internal loading in the sediment have been shown for certain lakes (Jeppesen et al, 2005).…”
Section: Duration Of Exposure To Hypoxia Matters For Biogeochemical Rmentioning
confidence: 99%
“…Subsurface-deposit feeders and large, deep-burrowing animals appear later in the recovery trajectory and then bioturbation and bio-irrigation activities are expected to increase. Biogeochemical modellers have employed linear and highly non-linear dependencies of bioirrigation and bioturbation depth and intensities on bottomwater oxygen levels (Morse and Eldridge, 2007;Soetaert and Middelburg, 2009). Katsev et al (2007) showed that additional knowledge about the response of bioturbation and bio-irrigation to hypoxia is necessary to further our predictive capabilities concerning the effect of oxygen on sediment biogeochemistry.…”
Section: Dynamics Of Faunal Response To Hypoxia and Sediment Biogeochmentioning
confidence: 99%
“…Together, the world-wide occurrence and spreading of coastal hypoxia create an imperative for improved biogeochemical models and understanding of linkages among ecosystem processes, which in turn will guide the development of new models and observational tools. It is expected that coupling of pelagic and benthic biogeochemical dynamics and ecosystem responses, and interaction with the atmosphere incorporated in coupled Earth Systems Models will be cross-linked in the next generation of models (Soetaert and Middelburg, 2009). Such an approach requires an increase in spatial and temporal resolution of observations and improvement in numerical techniques as well.…”
Section: Understanding the Causes Of Coastal Hypoxiamentioning
confidence: 99%
“…Long periods of hypoxia may induce complete elimination of fauna from sediments and result in the accumulation of organic matter and large stocks of iron sulfide. Restoration of bottom-water oxygen conditions may then not directly lead to full recovery of sediment ecosystem functioning because re-establishment of fauna may involve successions (Diaz and Rosenberg, 2008) and because accumulated sedimentary organic matter and sulfides may attenuate recovery processes (Soetaert and Middelburg, 2009;Middelburg and Levin, 2009). This may lead to hysteresis in the system response (Kemp et al, 2009 and Sect.…”
Section: Coastal Hypoxia and Benthic Biotamentioning
confidence: 99%
“…The factors controlling the formation of such authigenic minerals, which can act as a key sink for P in sediments of seasonally hypoxic basins, are still incompletely understood. This hampers accurate model projections of the recovery of eutrophic systems from hypoxia (Gustafsson et al 2012;Meier et al 2011;Soetaert and Middelburg 2009). …”
Section: Introductionmentioning
confidence: 99%